2016
DOI: 10.1042/bj20150586
|View full text |Cite
|
Sign up to set email alerts
|

Loss of neutral ceramidase protects cells from nutrient- and energy -deprivation-induced cell death

Abstract: Sphingolipids are a family of lipids that regulate the cell cycle, differentiation and cell death. Sphingolipids are known to play a role in the induction of apoptosis, but a role for these lipids in necroptosis is largely unknown. Necroptosis is a programmed form of cell death that, unlike apoptosis, does not require ATP. Necroptosis can be induced under a variety of conditions, including nutrient deprivation and plays a major role in ischaemia/reperfusion injury to organs. Sphingolipids play a role in ischae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 77 publications
(78 reference statements)
1
32
0
Order By: Relevance
“…The observed Asah2 mRNA reduction would serve to maintain ceramide and minimize the production of sphingosine [117], so it does not explain the sphingosine accumulation. A deficiency of nCDase protects from ER stress and from nutrient-deprivation-induced necroptosis via autophagy, while decreasing the formation of S1P at the plasma membrane [118][119][120], so this enzyme downregulation is in good agreement with the low S1P levels observed in the KIN cerebellum and may play a compensatory role.…”
Section: Utilization Of Ceramide In Atxn2-cag100-kin Mouse Tissuessupporting
confidence: 58%
“…The observed Asah2 mRNA reduction would serve to maintain ceramide and minimize the production of sphingosine [117], so it does not explain the sphingosine accumulation. A deficiency of nCDase protects from ER stress and from nutrient-deprivation-induced necroptosis via autophagy, while decreasing the formation of S1P at the plasma membrane [118][119][120], so this enzyme downregulation is in good agreement with the low S1P levels observed in the KIN cerebellum and may play a compensatory role.…”
Section: Utilization Of Ceramide In Atxn2-cag100-kin Mouse Tissuessupporting
confidence: 58%
“…All experiments were repeated at least twice with similar results; error bars represent SD of a single experiment. ***P , 0.001. empirically (and glucose as osmotic controls) to decrease HT-22 cell viability (39). Cell counts were not altered, even in the presence of 2-deoxyglucose (Supplemental Fig.…”
Section: Hsp27 Mutant Increases Autophagic Flux But Not Cellular Prolmentioning
confidence: 93%
“…Using a model of glycolysis inhibition via 2-deoxyglucose (2DG) and mitochondrial electron transport via antimycin A, Sundaram et al showed that loss of NC protected cells from nutrient deprivation-induced necroptosis via autophagy and clearance of damaged mitochondria (Sundaram et al, 2016). …”
Section: Neutral Ceramidase (Asah2 Asah2b Asah2c)mentioning
confidence: 99%